Optimasi Ekstraksi Minyak dan Karotenoid dari Limbah Serat Mesokarp Kelapa Sawit - Hotman Manurung; Donald Siahaan; Beinika Naibaho; Rosnawyta Simanjutak; Tumiur Gultom (Fakultas Teknik, 2021)
The purpose of this study was to determine the comparison of Palm oil Mesocarp Fiber (POMF) with hexane solvents and the optimal length of time when extracting oil by cold maceration method and to find out the optimization of carotenoid extraction from POMF oil. The study was conducted in 2 stages: The first stage of oil extraction from POMF with a hexane treatment ratio factor with the weight of POMF and extraction time. Using a non-factorial complete random design. Phase 2 Optimization of carotenoid extraction using the solvolytic method. Using a completely randomized design with 2 factors treatment, namely: 1 Type of minor solvent Methyl ester (Me) caprylic-capric fatty acid (C8 -C10) and Me lauricmyristic fatty acid (C12-C14) and minor solvent concentration of 0.1% and 0.25%. Parameters analyzedn in the first stage: oil content and Deterioration bleaching of index (DOBI). In the second stage the parameters are: carotenoid concentration, and DOBI. Optimal ratio of hexane to POMF weight is 1:40 (vol / g) with an oil content of 2.938%. Optimization of extraction time for 100 minutes with oil content of 4.104%. Optimization of carotenoid extraction from POMF oil is by using Me C8-C10 minor solvent with 0.1% amount of solvent which produces a carotenoid concentration of 302.444 ppm and a DOBI of 5.74. The increase in carotenoid concentration resulting from saponification reached 114.2 times that of carotenoid concentration in POMF oil.